2020
DOI: 10.3389/fonc.2020.00379
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Glutamic-Oxaloacetic Transaminase 1 Predicts Poor Prognosis in Acute Myeloid Leukemia

Abstract: One of the key features of acute myeloid leukemia (AML), a group of very aggressive myeloid malignancies, is their strikingly heterogenous outcomes. Accurate biomarkers are needed to improve prognostic assessment. Glutamate oxaloacetate transaminase 1 (GOT1) is essential for cell proliferation and apoptosis by regulating cell's metabolic dependency on glucose. It is unclear whether the expression level of GOT1 has clinical implications in AML. Therefore, we analyzed the data of 155 AML patients with GOT1 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In addition, altered gene expression is associated with the prognosis and may guide the treatment of AML patients. We found that AML patients with high expression of FHL2 , DDIT4 , GOT1 and iASPP tend to have shorter survival, while those with high expression of PAK2 and DOK7 have better outcomes ( 3 7 ). The role of epigenetics, which does not involve changes in DNA sequence, in leukemogenesis is of increasing concern.…”
Section: Introductionmentioning
confidence: 80%
“…In addition, altered gene expression is associated with the prognosis and may guide the treatment of AML patients. We found that AML patients with high expression of FHL2 , DDIT4 , GOT1 and iASPP tend to have shorter survival, while those with high expression of PAK2 and DOK7 have better outcomes ( 3 7 ). The role of epigenetics, which does not involve changes in DNA sequence, in leukemogenesis is of increasing concern.…”
Section: Introductionmentioning
confidence: 80%
“…GOT1 overexpression was shown to promote cisplatin resistance in NSCLC [ 20 ]. In acute myeloid leukemia, upregulation of GOT1 was also found to be associated with a worse prognosis [ 21 ]. However, in cervical cancer, upregulation of GOT1 mRNA is a protective factor, indicating a better prognosis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Leukemia, as a clinical disease with high morbidity and high mortality, its clinical research has not stopped [8,9] . However, But the speci c mechanism analysis is not clear, which brings great di culties to the prevention and treatment of leukemia and despite aggressive treatment, the prognosis of patients remains dismal [10] . MiRNAs plays an important role in the cancer development in leukemia [11,12] .…”
Section: Discussionmentioning
confidence: 99%